From a Pre-Service to an In-Service Tertiary EFL Teacher: An Autobiographical Narrative Inquiry - Arief Eko Priyo Atmojo (Universitas Islam Negeri (UIN) Mataram, 2021)
This autobiographical narrative inquiry study sheds some light on my career trajectory from a pre-service EFL teacher to an in-service tertiary EFL teacher. The data were garnered from written reflections on my lived experiences during initial teacher education program and seven years after graduation from initial teacher education program (2011-2021). Thematic coding was employed to analyze the data. The findings signified my career dynamics as a novice EFL teacher. It was challenging to find a permanent job as a teacher or lecturer. It was important for teachers to continuously develop themselves professionally through taking further formal education and training. The initial teacher education program enabled me to shape my character, personality, and identity as a teacher through formal classes and extra-curricular activities; and developed my professionalism through community, organization, competition, workshop, seminar, scientific work, and others. It was true that decisional capital played an essential role in teaching profession. It also indicated that struggle, patience, and endurance were important to endure in this teaching profession. This study signifies that an early career teacher must have other sources of income apart from their teaching profession, while waiting for a better and permanent teaching job. Future studies on the career trajectory of novice EFL teachers are still encouraged, particularly beyond the Indonesian context. Various research methods and designs may be applied to further study this issue.